Application of Eco Enzyme, Stunting Prevention, and Religious Moderation in Community Service Activities in Marubun Village, Sipispis District, Serdang Bedagai Regency - Siahaan, Edwansah Putra; Manik, Jahirun; Haris, Rizki Muhammad; Zuleika, Astrid Ola; Nabila, Fadya (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The application of eco enzyme as one of the innovations in the Real Work Lecture (KKN) activities that focus on stunting prevention and religious moderation. This study aims to explore how eco enzyme can be utilized as an environmentally friendly solution to improve public health, especially in efforts to prevent stunting in children. In addition, religious moderation activities are integrated to build social awareness and tolerance that support the success of health programs. The methods used include a participatory approach by involving the local community as the main actors in the production and utilization of eco enzyme, as well as a religious moderation discussion forum as a means of education and communication. The activity was implemented through the Real Work Lecture (KKN) UINSU 2025 program held in Marubun Village, Sipispis District, Serdang Bedagai Regency, which is a community service-based activity to Increase student empathy towards community and environmental conditions.